Air distribution system in rooms in the time of the plague - Cepiński, Wojciech; Szałański, Paweł; Misiński, Jacek (Instal, 2022)
The article indicates factors that increase and decrease the risk of airborne transmission of the pathogen in the room, using the SARS-CoV-2 experience as an example. In particular, the influence of the organization of air exchange in rooms on the risk of pathogen transmission was discussed, in dangerous situations – the presence of a sick person who may be a potential source of infection. Commonly used systems of organization of air exchange in rooms were analysed in terms of the possibility of the spread of contaminants or pathogens and their effective removal or elimination. The influence of devices such as air conditioners, portable fans and air purifiers was also considered. The most favourable solutions were identified, in line with the new paradigm of designing safe installations resulting from the coronavirus pandemic.